STRATEGI KOMUNIKASI BERBASIS KOMUNITAS DALAM PENERBITAN INDEPENDEN: STUDI KASUS MAKMOOD PUBLISHING - Agustrijanto Agustrijanto; Heppy New Year Haloho (Universitas Pelita Harapan, 2026)
Independent publishing industries face challenges related to the sustainability of manuscript production and the low participation of community-based writers, particularly among housewives who experience psychological barriers to writing activities. Self-perceptions of inadequacy and low confidence often hinder the involvement of this group in literacy practices. This study aims to analyze the community-based communication strategies developed by Makmood Publishing in fostering literacy participation through a community of housewife writers within the context of independent publishing. This study employs a qualitative approach with a case study design focusing on Makmood Publishing and the Makmood Community in Tangerang, Indonesia. Data were collected through in-depth interviews with managers and community members, limited participant observation of training and publishing activities, and analysis of institutional documents. The data were analyzed using thematic analysis to identify patterns of communication strategies and mechanisms for building literacy participation. The findings indicate that Makmood’s communication strategy is grounded in three main mechanisms. First, empathetic interpersonal communication is systematically used to address psychological barriers to writing and to strengthen members’ self-efficacy. Second, the community is positioned as the primary medium of marketing communication as well as a partner in manuscript production, resulting in collaborative and long-term relationships. Third, trust-based persuasive promotion functions to sustain participation, member loyalty, and the continuity of literacy content production. These findings demonstrate that the community does not merely function as a loyalty platform, but as a mechanism for value co-production and identity transformation within the independent publishing industry. Theoretically, this study extends the literature on community-based marketing by showing that community-based communication strategies operate as transformative relational practices that integrate marketing objectives with women’s literacy empowerment. Practically, this study offers a community-based communication strategy model that is relevant for independent publishers and literacy community managers in sustaining production continuity and writer participation.